Clostrìdìum botulinum - A cause of fish mortality - FOTIS (Γ. ΦΩΤΗΣ), G.; KIRKOUDIS (Ι. ΚΥΡΚΟΥΔΗΣ), I. (Journal of the Hellenic Veterinary Medical Society, 2018)
Clostridium botulinum type E proliferates in dead aquatic animals and sediments and it is distributed by water currents and infected fish. Botulism is a disease with great significance for both aquacultured fish and humans. The existing data about the subject are very few, and the aim of the present paper is to warn fish farmers and pathologists about the possibility of outbreaks in Greece.